Question
upstudy study bank question image url

Solve the following system of equations using an inverse matrix. You must also indicate the inverse matrix, \( A^{-1} \), that was used to solve the system. You may optionally write the inverse matrix with a scalar coefficient. \[ \begin{array}{r}-2 x-5 y=-6 \\ -x+y=8\end{array} \] Answer Attempt out of 2

Ask by Herrera Daniels. in the United States
Feb 04,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

The inverse matrix \( A^{-1} \) is: \[ A^{-1} = \begin{bmatrix} -\frac{1}{7} & -\frac{5}{7} \\ -\frac{1}{7} & \frac{2}{7} \end{bmatrix} \] Using this inverse matrix, the solution to the system is: \[ x = -\frac{34}{7}, \quad y = \frac{22}{7} \]

Solution

Sign in to Unlock Answers for Free!

A Learning Platform Trusted by Millions of Real Students and Teachers.

star-icon Unlock

Reviewed and approved by the UpStudy tutoring team

Mind Expander

First, let's represent the system of equations in matrix form. We can express it as \( AX = B \), where: \[ A = \begin{bmatrix} -2 & -5 \\ -1 & 1 \end{bmatrix}, \quad X = \begin{bmatrix} x \\ y \end{bmatrix}, \quad B = \begin{bmatrix} -6 \\ 8 \end{bmatrix} \] Next, we need to find the inverse of matrix \( A \). The formula for the inverse of a 2x2 matrix \( \begin{bmatrix} a & b \\ c & d \end{bmatrix} \) is given by: \[ A^{-1} = \frac{1}{ad - bc} \begin{bmatrix} d & -b \\ -c & a \end{bmatrix} \] For our matrix \( A = \begin{bmatrix} -2 & -5 \\ -1 & 1 \end{bmatrix} \), we can calculate the determinant \( ad - bc \): \[ \text{det}(A) = (-2)(1) - (-5)(-1) = -2 - 5 = -7 \] Now we can calculate \( A^{-1} \): \[ A^{-1} = \frac{1}{-7} \begin{bmatrix} 1 & 5 \\ 1 & -2 \end{bmatrix} = \begin{bmatrix} -\frac{1}{7} & -\frac{5}{7} \\ -\frac{1}{7} & \frac{2}{7} \end{bmatrix} \] Now we can solve for \( X \): \[ X = A^{-1}B = \begin{bmatrix} -\frac{1}{7} & -\frac{5}{7} \\ -\frac{1}{7} & \frac{2}{7} \end{bmatrix} \begin{bmatrix} -6 \\ 8 \end{bmatrix} \] Calculating this product, we find: \[ X = \begin{bmatrix} -\frac{1}{7}(-6) + -\frac{5}{7}(8) \\ -\frac{1}{7}(-6) + \frac{2}{7}(8) \end{bmatrix} = \begin{bmatrix} \frac{6}{7} - \frac{40}{7} \\ \frac{6}{7} + \frac{16}{7} \end{bmatrix} = \begin{bmatrix} -\frac{34}{7} \\ \frac{22}{7} \end{bmatrix} \] Thus, the solution is: \[ x = -\frac{34}{7}, \quad y = \frac{22}{7} \] The inverse matrix used is: \[ A^{-1} = \begin{bmatrix} -\frac{1}{7} & -\frac{5}{7} \\ -\frac{1}{7} & \frac{2}{7} \end{bmatrix} \]

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy